Performance Analysis of PFI using FP-Growth Algorithm for various Data-sets - Shital A, Patil; Potgantwar, Amol (International Journal of Computer Sciences and Engineering, 2025)
The data handled in appearing applications like placement or situation based services, sensor monitoring systems, and data integration, are often not exact in nature. In this article, we study the important problem of extracting frequent item sets[1] from a huge unsure database, illuminated under the Possible World Semantics (PWS)[2].This issue is technically challenging, since an unsure database consist an exponential number of possible worlds. By observing that the mining process can be show as a discrete probability distribution, we develop an FP Growth algorithm [4] which compress a large database into a dense, Frequent-Pattern tree (FP-tree) [4] structure also Develop an efficient, FP-tree-based frequent pattern mining method (FP-growth) and Apriori algorithm for frequent item set mining. We also study the important problem of maintaining the mining result for a database that is developing (e.g. by inserting a tuple). Specifically, we present incremental mining algorithms [13], which enable Probabilistic repeated Item set (PFI) results to be refreshed. This decrease the requirement of re-executing the whole mining algorithm on the new database, which is often more expensive and unnecessary. We observe how an existing algorithm that retrieves exact item sets, as well as our approximate algorithm, can support incremental mining. All our algorithms support both tuple and attribute uncertainty, which are two common uncertain database models. We also perform huge evaluation on real and synthetic data sets to validate our approaches.